Kebijakan Jejamou Ngebangun Sai Bumi Nengah Nyappur di Kabupaten Tulang Bawang, Lampung - Agus Mardihartono (Jurnal Studi Pemerintahan, 2011)
This study aims to explain the local wisdom in Tulang Bawang region, based on the cultural richness Megaou Pak (four Marga) in Lampung, which consists of Piil Senggeri philosophy of life. Where in the Piil Senggeri consists of Bajuluk Baadek (award), Nemui Nyimah (receiving guests and reward), Nengah Nyappur (mix and interact with others) and Sakai Sambayan (mutual aid). The study found that local wisdom can actually be a driving force in local policy-making level, only local wisdom is often not understood in depth so it can not be implemented in regional development policy. There are several issues that the constraints which are still not optimal utilization of human resources are qualified, bureaucrats and public understanding is still lacking, as well as the institutionalization oflocal wisdom that is still less so as not to be an important part in regional development.